2004
DOI: 10.1111/j.0732-8516.2004.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Pricing Efficiency in a Thin Market with Competitive Market Makers: Box Spread Strategies in the Hang Seng Index Options Market

Abstract: Using a box spread arbitrage strategy, we examine the pricing efficiency of the emerging, thinly traded Hang Seng Index options market in Hong Kong, where market makers operate under a competitive open outcry system. In 20 months of tick-by-tick bid-ask and transaction quotes we find very few arbitrage opportunities. Our examination of the reporting time of quotes shows that in effect, all the apparent mispricings are deceptive and could be explained by stale quotes. The absence of real arbitrage opportunities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…Often an abnormally high excess return (higher than 100%) is also available. These results are contrary to the results of most similar studies carried out with the high-frequency data and European options (for instance, refer to Benzion et al, 2005;Bharadwaj & Wiggins, 2001;Fung et al, 2004). Only Hemler and Miller (1997), for postcrash period, have similar findings.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Often an abnormally high excess return (higher than 100%) is also available. These results are contrary to the results of most similar studies carried out with the high-frequency data and European options (for instance, refer to Benzion et al, 2005;Bharadwaj & Wiggins, 2001;Fung et al, 2004). Only Hemler and Miller (1997), for postcrash period, have similar findings.…”
Section: Resultscontrasting
confidence: 99%
“…Benzion et al (2005) identify 4,505 profitable box spreads. Fung et al (2004) construct 5,783 box spreads. Hemler and Miller (1997), using 38,000 quotations, identify about 2,700 profitable box spreads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even after making the assumption of no transaction costs, they found very few low-profit arbitrage opportunities. Fung et al 2004 in their study examined the pricing efficiency of Hang Seng Index options market in Hong Kong, which is an emerging market and thinly traded, by making use of Box spread Strategy. The study was based on 20 months of tick-by-tick bid-ask and transaction quotes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, studies have found that market prices increase with the level of quality uncertainty under monopolistic competition and monopoly (Bagwell and Riordan 1991;Dranove and Satterthwaite 1992), that different types of market structures often influence how price changes (Axarloglou 2007;Carlton 1986;Domberger and Fiebig 1993), and that price formation in securities markets can be (Biais 1993;Easley et al 1996;Easley and O'Hara 1987;Fung et al 2004). It should be noted, however, that online auctions are substantially different from traditional auctions; which typically attract a small number of participants who often need to be physically present, involve high transaction costs, and offer a limited scope of items that typically are non-standardized.…”
Section: Introductionmentioning
confidence: 99%